Transformasi Program Bimbingan Konseling Berbasis Need Assessment dan Evaluasi Digital - Renidayati Reni; Yarmis Syukur; Netrawati Netrawati (Poltekkes Kemenkes Padang, 2026)
Guidance and counseling programs in senior high schools need to transform from administrative-oriented services into data-based, developmental, and digitally evaluated services. This study aims to analyze the transformation of the guidance and counseling program based on need assessment and digital evaluation at SMAN 1 Padang. This study used a descriptive qualitative approach. Data were collected through interviews with a school counselor and document review of the guidance and counseling program. The results showed that the guidance and counseling program at SMAN 1 Padang has been developed based on students’ needs through several assessment instruments, including AUM, AUM PTSDL, questionnaires, sociometry, observation, interviews, and academic data. The program includes basic services, responsive services, individual planning, and system support. A notable innovation is the use of digital evaluation through online rubrics and student feedback links. However, several challenges remain, including a high student-counselor ratio, limited classroom guidance hours, inadequate counseling room facilities, and uneven understanding of counseling functions among subject teachers. This study concludes that need assessment and digital evaluation are important strategies to strengthen the quality, accountability, and relevance of modern school counseling services